The current state and trends of air transport as factors of the labor market structural changes in aviation business - U. U. Mihalchevsky (Вестник СибАДИ)
The article describes the relevance of the study in the current state and trends of air transportation. We have established the relationship of transport services market, the labor market and the education market in the aviation sector. Air transport market is characterized by ups and dips in traffic. Changing of transportation structure under the influence of external factors are significant. The article illustrates the air transport services market statistics and changes in the market of aviation personnel. We gave an overview of the aviation market research and conclusions of Boeing company, and systematized factors on labor market trends depending of the air transport market.